2022
DOI: 10.1007/s00265-022-03270-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple parasitism in an evictor brood parasite: patterns revealed by long-term monitoring, continuous video recording, and genetic analyses

Abstract: In some populations of host of brood parasites, more than two parasite eggs may be laid in a single nest. This phenomenon is known as multiple parasitism, representing a cost to both host and parasite. In this study, we analysed a long-term dataset (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021) focusing on multiple parasitism of the common cuckoo (Cuculus canorus) parasitizing the great reed warbler (Acrocephalus arundinaceus). Annual parasitism rate was on average 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The desertion rate of all experimentally parasitized nests was significantly lower than that of naturally parasitized nests during the early egg-laying stage, particularly in Group 2, which could be attributed to the different parasite encounters during the two processes, 7 , 11 , 28 , 65 as natural parasitism entails diverse cues, and the levels of exposure to these cues are different from those experienced during experimental conditions. For example, multiparasitised nests are more likely to be abandoned, 66 which could be related to multiple nest visits by cuckoos. We also observed that nests with four to five eggs were parasitized only after frequent parasitism attempts and host attacks, eventually leading to nest desertion.…”
Section: Discussionmentioning
confidence: 99%
“…The desertion rate of all experimentally parasitized nests was significantly lower than that of naturally parasitized nests during the early egg-laying stage, particularly in Group 2, which could be attributed to the different parasite encounters during the two processes, 7 , 11 , 28 , 65 as natural parasitism entails diverse cues, and the levels of exposure to these cues are different from those experienced during experimental conditions. For example, multiparasitised nests are more likely to be abandoned, 66 which could be related to multiple nest visits by cuckoos. We also observed that nests with four to five eggs were parasitized only after frequent parasitism attempts and host attacks, eventually leading to nest desertion.…”
Section: Discussionmentioning
confidence: 99%
“…), limit host offspring survival through competitive exclusion ( Soler 2017 ) or direct killing ( Honza et al 2007 ; Spottiswoode and Koorevaar 2012 ), in many cases resulting in the parasitic chick becoming the sole occupant of the nest. Concurrent (i.e., multiple or repeated) parasitism by two or more brood parasitic offspring within a single host clutch ( Gloag, Fiorini, et al 2012 ) is more commonly reported from brood parasites with a low impact on host offspring survival and condition ( Martínez et al 1998 ; Tuero et al 2007 ; Goguen et al 2011 ) than from virulent parasites ( Marton 2021 ; Honza et al 2022 ). This situation arises because high virulence is associated with increased competition for host resources, leading to poor survival prospects for the younger parasite ( Moskát and Honza 2002 ; Spottiswoode 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Acrocephalus warblers are among the most wellstudied cuckoo host genera [14,[23][24][25][26][27]]. As a prominent example of coevolutionary arms race [28], the warblercuckoo coevolution is often assumed to have had sufficient time to adapt both egg rejection and egg colour mimicry via coevolutionary arms races [14,29,30].…”
Section: Introductionmentioning
confidence: 99%